Land use/land cover forecasting of future development and its impact on hydrological response in monsoonal catchment area of Kelantan, Malaysia / Noor Syafiqah Che Omar - Che Omar, Noor Syafiqah (2016)
Land use/land cover (LU/LC) change is related to the human need and demand such as residential, industrial, and commercial. As urban land development increase, the condition of the land surface may vary. Varies in land surface will assign negative impact to surrounding nature, such as flood occurrence in term of runoff. Therefore, this research attempts to study the cause and effect between LULC and runoff changes based on simulated future scenario analysis using geospatial-hydrological modelling approaches. The objectives of this study are i) to analyse suitability factors for future urban land development with the aid of the GIS planning support system software (i.e. Arc GIS 9.3 and What-if? 2.0), ii) to produce map of suitability and allocation areas for future land use development of Kelantan sub-basins (2020s, 2030s, 2040s and 2050s) and, iii) to simulate and quantify hydrologic responses changes of event-based rainfall due to simulated future land use changes (2020s, 2030s, 2040s,2050s) through hydrological modelling (i.e. HEC-HMS).The first analysis performed was to define the suitable area to be developed based on the selected factors which are slope, river, urban buffer, road network and demography data (i.e. population and employment information). Those factors were used in presenting the suitability of land area to be developed as low, moderate and high development scenario. Referring to the simulation of the future land development projection analysis through What-if? Software, the projected land use area such as forest, agriculture and built-up area are changing from the baseline years of 2010. Each sub-basin (i.e. Nenggiri, Galas, Pergau., Lebir, Kuala Krai and Guillemard Bridge) show the increase in built-up land development from a baseline 2010. Meanwhile, the forest and agriculture land area show the decrease value for every sub-basin area either for low, moderate or high development scenario. The Lebir sub-basin shows the highest increased in the projected built-up land in the year of 2050 with 69.70% based on the high development scenario. Meanwhile, the Nenggiri sub-basin stated the lowest projected built-up land area of 0.98% based on the high development scenario. Subsequently, the result obtained in the second objectives was used in the final analysis of the impact projection land use land cover in the future flooding. The result reveals that the high development scenario contributes to the predicted changes in peak discharge is increasing at downstream area. The Lebir sub-basin recorded increasing of flood occurrence at 36.39%, meanwhile, for the runoff is recorded to increase by 41.45%. Meanwhile, the low land development scenario predicted changes in peak discharge is increasing at upstream area. The Pergau sub-basin recorded'the increasing rate of peak discharge at 19.53% and for runoff volume recorded increasing value at 20.73%. Therefore, this study provides an indicator of what will occur in the future if such projected land use land cover development using geospatial analysis were taken place. Thus, concrete the evidence that changes in land use land cover have brought the negative impact to the flood occurrence. This study is benefited in the decision making process, particularly for the urban planner as well as water resources manager in relation to reduce flood impact in the future.